2019
DOI: 10.7759/cureus.6078
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes of a Surgical Technique in Management of Subconjunctival Orbital Fat Prolapse

Abstract: ObjectiveThis retrospective, single-center, interventional study presented the long-term results of a novel surgical technique for the management of subconjunctival orbital fat prolapse.MethodsNine eyes of seven consecutive patients were surgically repaired using the technique involving connective tissue repair and were intended to be followed-up for more than five years.ResultsAll surgeries performed were uneventful and esthetic enhancement was achieved for each patient. No postoperative complications were no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Previous studies have shown that more than 75% of patients with SHOF in the superotemporal quadrant were male. [2–4,6,7,9,14,15] In our experience, 40 out of the 44 patients (90.9%) with SHOF in the superotemporal quadrant were male. In addition, previous studies have shown that 38.5-76% of the cases were obese.…”
Section: Discussionmentioning
confidence: 62%
“…Previous studies have shown that more than 75% of patients with SHOF in the superotemporal quadrant were male. [2–4,6,7,9,14,15] In our experience, 40 out of the 44 patients (90.9%) with SHOF in the superotemporal quadrant were male. In addition, previous studies have shown that 38.5-76% of the cases were obese.…”
Section: Discussionmentioning
confidence: 62%
“…It is important to distinguish ocular lymphoma, whether primary or metastatic, from several key conditions 1,[4][5][6][7][8][9][10][11] (Table 1).…”
Section: Differential Diagnosismentioning
confidence: 99%
“…4 Overall survival for patients with relapsed mantle cell lymphoma manifesting in the orbit was 4.1 years. 15 Bilateral or unilateral 9 Appearance Vascularized, pink bullous mass in superior or inferior conjunctiva 8 or vascularized, salmon colored, swollen lacrimal gland (rare) 11 Yellow mobile mass in superior temporal conjunctiva 10 Pink-yellow, nonmobile mass at lateral canthus 4 Yellow mass in superior lateral conjunctiva with superficial fine vessels 7 Diagnosis Medical history, hematology studies, biopsy, PET/MRI 9 Clinical appearance 6 Clinical appearance 4 Hematology and endocrinology studies 9 PET = positron emission tomography.…”
Section: Prognosismentioning
confidence: 99%